The Italian breakthrough in CRISPR trials for rare diseases: a focus on beta-thalassemia and sickle cell disease treatment - Greco, Francesca; Cosentino, Marco; Marino, Franca (Frontiers in Medicine, 2024)
The development of gene therapy and the current advantageous method of clustered regularly interspaced short palindromic repeats (CRISPRs) has allowed the implementation of several clinical trials aimed at studying the possible efficacy of gene therapy for rare diseases. Rare diseases pose a global challenge, in that their collective impact on health systems is considerable, whereas their individually rare occurrence hinders research and development of efficient therapies. Despite the low prevalence of individual rare diseases, there are more than 7,000 defined rare diseases affecting 3.5–5.9% of the global population. Rare diseases are mostly chronic and approximately 80% are caused by genetic mutation with an early-life onset. In Italy, in 2021 were recorded more than 400,000 people with rare disease. Because of its location and history, Italy has an unfortunate statistic regarding the presence and prevalence of two rare genetic diseases, namely beta-thalassemia, of which there are about 90 million carriers worldwide, 400,000 of whom are actually affected, and sickle cell disease, with about 300 million carriers and 6.5 million people affected worldwide. Advancements in genomic studies allowed Italy to join clinical trials to study effective and resolving gene therapies for BT and SCD. This study reports on the impact of rare diseases in Italy, ongoing studies, and recent achievements in BT and SCD trials using the CRISPR method and remaining hurdles in the application of CRISPR technology to rare diseases, also taking a glimpse at the newest challenges and future opportunities in the genetic treatment for rare diseases.